2009
DOI: 10.1093/nar/gkp732
|View full text |Cite
|
Sign up to set email alerts
|

An analytical platform for mass spectrometry-based identification and chemical analysis of RNA in ribonucleoprotein complexes

Abstract: We describe here a mass spectrometry (MS)-based analytical platform of RNA, which combines direct nano-flow reversed-phase liquid chromatography (RPLC) on a spray tip column and a high-resolution LTQ-Orbitrap mass spectrometer. Operating RPLC under a very low flow rate with volatile solvents and MS in the negative mode, we could estimate highly accurate mass values sufficient to predict the nucleotide composition of a ∼21-nucleotide small interfering RNA, detect post-transcriptional modifications in yeast tRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
82
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(82 citation statements)
references
References 77 publications
0
82
0
Order By: Relevance
“…High voltage for ionization in negative mode (−1.4 kV) was applied to the metal union, and the eluate from RPLC was Affinity Proteomics J Proteomics Bioinform ISSN: 0974-276X JPB, an open access journal sprayed on-line to an LTQ-Orbitrap hybrid mass spectrometer (model XL, Thermo Fisher Scientific, San Jose, CA). Reverse phase separation of oligoribonucleotides was performed at flow rate of 100 nl/min using a 30-min linear gradient from 10 to 40% methanol in 10 mM triethylammonium acetate (pH 7.0).The mass spectrometer was operated in a data-dependent mode to automatically switch between Orbitrap-MS and linear ion trap-MS/MS acquisition as described [35]. Survey full scan MS spectra (from m/z 500 to 1,500) were acquired in the Orbitrap with resolution R=30,000 (after accumulation to a target value of 500,000 ions in the linear ion trap).…”
Section: Lc-ms/ms Apparatus For Rna Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…High voltage for ionization in negative mode (−1.4 kV) was applied to the metal union, and the eluate from RPLC was Affinity Proteomics J Proteomics Bioinform ISSN: 0974-276X JPB, an open access journal sprayed on-line to an LTQ-Orbitrap hybrid mass spectrometer (model XL, Thermo Fisher Scientific, San Jose, CA). Reverse phase separation of oligoribonucleotides was performed at flow rate of 100 nl/min using a 30-min linear gradient from 10 to 40% methanol in 10 mM triethylammonium acetate (pH 7.0).The mass spectrometer was operated in a data-dependent mode to automatically switch between Orbitrap-MS and linear ion trap-MS/MS acquisition as described [35]. Survey full scan MS spectra (from m/z 500 to 1,500) were acquired in the Orbitrap with resolution R=30,000 (after accumulation to a target value of 500,000 ions in the linear ion trap).…”
Section: Lc-ms/ms Apparatus For Rna Analysismentioning
confidence: 99%
“…LC was performed at a flow rate of 100 nl/ min using a 30-min linear gradient from 10% to 40% methanol in 10 mM triethylammonium acetate (pH 7.0). The mass spectrometer was operated in a mode to automatically switch between Orbitrap-MS and linear ion trap-MS/MS acquisition as described [35].…”
Section: Lc-ms/ms Apparatus For Rna Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Huber and coworkers have optimized the utility of monolithic capillary columns packed with octadecyl poly(styrene/divinylbenzene) particles as the stationary phase and gradients of acetonitrile in 25 mM TEAB as the mobile phase to analyze a diverse assortment of synthetic and biological oligonucleotides [67,71]. Recently Taoka et al reported the use of nanoelectrospray LC-MS for the analysis of synthetic siRNA [72]. They used a 50 mm × 150 µM i.d.…”
Section: Lc-ms Techniquesmentioning
confidence: 99%
“…We used nano-flow liquid chromatography (LC) and high-resolution hybrid mass spectrometry (MS) coupled with a data analysis system [Taoka et al, 2009] to measure the amount of individual r-proteins in the ribosome of the yqgF ts mutant and compared the data with those of an isogenic yqgF + strain. To prepare 70S ribosomes for this analysis, we subjected yqgF + cells to growth in M9 minimal medium containing 15 NH 4 Cl, and subsequently prepared 15 N-labeled 70S ribosomes (Fig.…”
mentioning
confidence: 99%